Decision Support System Decision Support System To Determine Sports Interest and Talent Using the Bayes Method - Mhd Furqan; Yusuf Ramadhan Nasution; Fahrul Azis Nasution (Sean Institute, 2021)
The identification of talent interests has been developed and its benefits have been felt in producing athletes who can excel at the national and international levels. Decision support system can be chosen because it is an appropriate way to determine interest and talent in sports, basically the concept of a decision support system is limited to activities to help assess a decision. In this study, using the Bayes method with this method requires probability information on each alternative to the problems faced to produce an expected value as a basis for decision making. The trial of calculations using the Bayes method on 50 samples of students who were successfully tested, namely 18 students with interests and talents in soccer, 13 gifted students in volleyball, 9 gifted students in badminton, 6 students who are gifted in sports. basketball, 4 gifted students in table tennis. In the application of the decision support system to determine interests and sports talents has been successfully made and running well to assist and facilitate the decision-making process of sports interests and talents.